Hyperrealism and Other Indigenous Forms of 'Faking It with the Truth'1. Issue 1 (May 2018) - Biddle, Jennifer L.; Lea, Tess
Abstract : This essay introduces Visual Anthropology Review's Hyperrealism and Other Indigenous Forms of 'Faking It with the Truth, ' a special collection of essays on new media art, ceremony, animation, sensory immersion, and other hyperreal interventions by Aboriginal and First Nations artists, curators, and academics. This essay introduces the contributing Indigenous and non‐Indigenous authors who are working across this emergent field of cultural production. Developing key concepts in critical dialogue with Indigenous practice‐based activism and history, it argues that works of the Indigenous hyperreal serve to challenge dominant frameworks of anthropology and canonical art theory. It provides historical and conceptual background for understanding the importance of these works as vital strategies of survival taking shape in neocolonial contexts across Indigenous territories of Australia and Turtle Island today.